RANCANGAN MESIN PENGHANCUR KOHE KAMBING UNTUK PUPUK - reza; Ardiansyah , Reza; Qibran, Muhammad Agil (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Goat feces (kohe) can be used as kohe fertilizer. However, goat kohe that is directly sown takes a long time to decompose due to its hard texture. From these problems, the design of an efficient chopping machine kohe is made which can accelerate the fermentation process in goat kohe. The design method used refers to the VDI 2222 method, namely analysis, planning, conceptualizing and designing. The results of the machine design have dimensions of 1000x500x565 mm, a capacity of 250 kg / hour, using a 7.5 HP fuel motor, a pulley and belt transmission system with a speed of 3000 RPM input and an output RPM of 903 RPM. This machine is equipped with 28 removable crushing knives and a filter that functions to smooth the goat's kohe. The analysis and simulation results show that the designed shaft has a theoretical stress stress of 2,204 N/mm2 and a simulation of 2,280 N/mm2. Displacement analysis on the shaft theoretically amounted to 0.00645 mm and simulation amounted to 0.00514 mm. The strain analysis on the shaft was theoretically 0.00001075 mm and simulation was 0.0000927 mm and the stress on the crushing blade was theoretically 0.446 N/mm2 and simulation was 0.776 N/mm2. Strain analysis of the crushing blade theoretically amounted to 2.124 mm and simulation amounted to 2.242 mm. The displacement analysis of the crushing blade theoretically amounted to 0.000219 mm and the simulation amounted to 0.000213 mm which indicates that the designed crushing blade is safe.